Prevalence and risk factors of current hepatitis C infection among men who have sex with men aged 20–59 years: NHANES 1999–2016 - Yan Zhang; Jiewei Liu; Yihao Lin; Agins Bruce; Yangyang She; Hongbo Jiang (Sexual Health, 2026)
Background Men who have sex with men (MSM) are a key population with a higher prevalence of hepatitis C virus (HCV) infection than the general population. Our study estimated the prevalence of current HCV infection and identified risk factors among MSM aged 20–59 years in the US from 1999 to 2016. Methods Data were obtained from the 1999–2016 National Health and Nutrition Examination Survey (NHANES). Current HCV infection was defined as having a positive HCV RNA test result. The prevalence of current HCV infection was weighted according to the complex survey design of NHANES. A Rao–Scott Chi-squared test was used to compare the differences between HCV-positive and HCV-negative MSM. Multivariable logistic regression was used to identify risk factors for current HCV infection. Results In the US, nearly 5.1% (95% CI 4.5–5.7) of the general population self-reported as MSM. The weighted prevalence of current HCV infection was 1.8% (95% CI 1.5–2.1) among non-institutionalized US males, and 3.5% (95% CI 1.9–5.7) among MSM. Current HCV infection among MSM was associated with injection drug use (aOR 29.2, 95% CI 12.1–70.8), blood transfusion (aOR 8.2, 95% CI 1.5–45.7), being aged 40–59 years (aOR 4.0, 95% CI 1.6–10.1) and having a poverty income ratio <1.0 (aOR 5.8, 95% CI 1.3–25.2). Conclusions In the US, the prevalence of current HCV infection is nearly twice as high among MSM as among males in the general population, suggesting the need for surveillance of the HCV epidemic among MSM. Prevention and control strategies targeting the risk factors are critical to combating the HCV epidemic among MSM.